2004
DOI: 10.1523/jneurosci.3294-03.2004
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Axonal Extension and Growth Cone Motility by Calmodulin-Dependent Protein Kinase I

Abstract: Calcium and calmodulin (CaM) are important signaling molecules that regulate axonal or dendritic extension and branching. The Ca 2ϩ -dependent stimulation of neurite elongation has generally been assumed to be mediated by CaM-kinase II (CaMKII), although other members of the CaMK family are highly expressed in developing neurons. We have examined this assumption using a combination of dominant-negative CaMKs (dnCaMKs) and other specific CaMK inhibitors. Here we report that inhibition of cytosolic CaMKI, but no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
182
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 173 publications
(191 citation statements)
references
References 66 publications
9
182
0
Order By: Relevance
“…Lamellipodia are known to play a crucial role in growth cone motility (Dickson, 2002). Thus, it has been proposed that lamellipodia might help to stabilize growth cones and promote neurite elongation (Wayman et al, 2004). Consistent with this idea, we found that GABA promotes stabilization of newly formed dendritic segments, thereby inducing a net elongation of dendrites.…”
Section: Discussionsupporting
confidence: 87%
“…Lamellipodia are known to play a crucial role in growth cone motility (Dickson, 2002). Thus, it has been proposed that lamellipodia might help to stabilize growth cones and promote neurite elongation (Wayman et al, 2004). Consistent with this idea, we found that GABA promotes stabilization of newly formed dendritic segments, thereby inducing a net elongation of dendrites.…”
Section: Discussionsupporting
confidence: 87%
“…It seems likely that differential activation of calcium frequency-dependent effectors such as CaMKII and calcineurin would occur in each axonal process. Positive effectors such as CaMKI and CaMKII, which have been shown to promote neurite outgrowth (Borodinsky et al, 2003;Wayman et al, 2004Wayman et al, , 2006 are preferentially activated in axonal processes with higher frequencies of Ca 2ϩ transients (Tang and Kalil, 2005). CaMKII␤ has been shown to bind directly to actin filaments and increase filopodial dynamics (Fink et al, 2003), consistent with results indicating that direct elevation of Ca 2ϩ activity by photolysis of caged calcium can rapidly evoke protrusion of new filopodia through polymerization of actin filaments (Lau et al, 1999).…”
Section: Branching Of Cortical Neurons In Vitro Reflects In Vivo Bransupporting
confidence: 59%
“…One study also showed the enzyme encoded by CAMKK2 can phosphorylate AMP-activated protein kinase. 68 The CAMKK2 gene has the strongest expression in brain 31 and it influences signaling cascades that are involved with learning and memory, 32,69 neuronal differentiation and migration, 70 neurite outgrowth 34,35,70 and synapse formation.…”
Section: Resultsmentioning
confidence: 99%
“…CAMKK2 can promote neurite outgrowth during brain development and inhibition of CAMKK2 inhibits neurite outgrowth and causes axonal growth cone collapse. 34,35 In addition, transgenic studies performed in mice have shown that CAMKK2 is required for late long-term potentiation (LTP) in the hippocampus and spatial memory formation. 32 Furthermore, previous studies have revealed that CAMKK2 is required for the activation of hippocampal cyclic AMPresponsive element-binding protein (CREB) by spatial training, 32 a key step in long-term memory formation.…”
Section: Introductionmentioning
confidence: 99%